Disaster risk reduction among households exposed to landslide hazard: A crucial role for self-efficacy?. (June 2018) - Mertens, K.; Jacobs, L.; Maes, J.; Poesen, J.; Kervyn, M.; Vranken, L.
Graphical abstract: Highlights: Farmers that are more exposed to landslide risk have a lower intention to plant trees. Awareness about landslide threat is high. Perceived suitability of trees for landslide risk reduction is also high. Self-efficacy is low among those households that have a low willingness to plant trees. A non-protective response trap is proposed to explain our results. Abstract: Natural hazards have a large impact on household livelihoods worldwide, especially in the Global South. Yet, literature on the adoption of risk reduction measures at household level remains scattered and inconclusive. This study combines geographical data with an original cross-sectional household survey to investigate the relation between individual land use plans and both exposure to and experience with a natural hazard. Regressions are used to test the protection motivation theory (PMT) and to investigate the link between intentions to plant trees to reduce landslide risk and past experiences, actual exposure, perceived threat and perceived capacity to prevent the occurrence of landslides. The results show that respondents in our study area in Uganda are well aware of landslide risk and believe trees are effective in landslide susceptibility reduction. Yet, those farmers that would benefit most from reducing landslide susceptibility by planting trees have the lowest intention to do so. A low self-efficacy among exposed farmers is proposed to explain this result. This finding has important implications for disaster risk reduction and land use policies and leads to recommendations on how governments and development agents should communicate about landslide risk.